Birnessite Nanosheet Arrays with High K Content as a High‐Capacity and Ultrastable Cathode for K‐Ion Batteries. Issue 24 (2nd May 2019) - Lin, Baowei; Zhu, Xiaohui; Fang, Lingzhe; Liu, Xinyi; Li, Shuang; Zhai, Teng; Xue, Liang; Guo, Qiubo; Xu, Jing; Xia, Hui
Abstract: Potassium‐ion batteries (PIBs) are one of the emerging energy‐storage technologies due to the low cost of potassium and theoretically high energy density. However, the development of PIBs is hindered by the poor K + transport kinetics and the structural instability of the cathode materials during K + intercalation/deintercalation. In this work, birnessite nanosheet arrays with high K content (K0.77 MnO2 ⋅0.23H2 O) are prepared by "hydrothermal potassiation" as a potential cathode for PIBs, demonstrating ultrahigh reversible specific capacity of about 134 mAh g −1 at a current density of 100 mA g −1, as well as great rate capability (77 mAh g −1 at 1000 mA g −1 ) and superior cycling stability (80.5% capacity retention after 1000 cycles at 1000 mA g −1 ). With the introduction of adequate K + ions in the interlayer, the K‐birnessite exhibits highly stabilized layered structure with highly reversible structure variation upon K + intercalation/deintercalation. The practical feasibility of the K‐birnessite cathode in PIBs is further demonstrated by constructing full cells with a hard–soft composite carbon anode. This study highlights effective K + ‐intercalation for birnessite to achieve superior K‐storage performance for PIBs, making it a general strategy for developing high‐performance cathodes in rechargeable batteries beyond lithium‐ion batteries. Abstract : Birnessite‐K0.77 MnO2 ⋅0.23H2 O nanosheet arrays with high K content are proposed as high‐performance cathode for potassium‐ion batteries. Due to the adequate K + ions in the interlayer, the K + ‐ion diffusion kinetics is enhanced and the structure degradation is effectively suppressed, resulting in a high specific capacity, excellent rate capability, and ultrahigh stability upon repeated potassiation/depotassiation.